Adoption of Scientific Pig Production Practices by Small Scale Pig Farmers in Assam: A Comparative Analysis - Madhavan, Misha M.; Mohan, Narayana H.; Barman, Keshab; Gupta, V. K.; Pator, Sunil; Chutia, Priyanka; Chetri, Trilochan Karki (Indian Journal of Extension Education, 2022)
The research work was undertaken to compare the adoption of scientific pig production practices by small scale pig farmers in Assam in the adopted villages of ICAR-National Research Centre on Pig, Guwahati and the non-adopted villages. A composite adoption index was developed for measuring the adoption level of small-scale pig farmers. The primary data was collected from 360 small scale pig farmers equally from both the groups during 2020-2021. The data was analyzed using Mann-Whitney “U” test and observed a significant difference in adoption level between both the groups. In the adopted villages, 50.56 per cent of farmers were under high adoption category followed by 48.89 per cent in medium category whereas in non-adopted villages, about 88.33 per cent of the respondents were in the low adoption category and 10.56 per cent in medium adoption category. The independent factors like education, experience in pig farming, family size, herd size, annual income, extension contact and social participation were positively correlated with adoption level. It was observed that the adoption level of scientific pig production practices by small scale pig farmers in adopted villages is significantly higher than the adoption level of non-adopted villages.
Keywords: Adoption index; Pig production; Small scale pig farmers; Adopted villages; Scientific practices